The Influence of Indirect Democracy and Leadership Choice on Cooperation - Fanny E. Schories (Experimental Economics, 2022)
The paper examines whether an institution has a differing impact on cooperation if it is introduced by a representative of the affected subjects rather than exogenously imposed. The experimental design controls for selection effects arising from the endogenous policy choice. The treatment varies whether the decision-maker is elected or randomly appointed. There is evidence of a large democracy premium in the sense that endogenously chosen institutions lead to more cooperation than identical exogenous institutions, but only if the group leader is democratically chosen. Especially the subjects who initially did not prefer the policy are more likely to cooperate if it was brought about by an elected representative. There is no democracy premium for randomly appointed group leaders.
Keywords: C9; D02; D72; 330; Laboratory experiment; Representative democracy; Collective decision-making; Social dilemma; Legitimacy